Current situation of the tola’s shrubs in San Jose de Aymara, Huancavelica - Peru - Solange Montero , Terry (2022)
The native bushes/shrubs are part of the Andean landscape. They are used to protect the ground and improve soil conditions, and in the highlands in the south of the country some of them are used as all year-round firewood, especially during the wet season. This article includes an update of the situation of the "tolas" planted in the Andean community of San Jose de Aymara and the results of a small survey developed in 2020. The visit to the community confirmed that the tolas remain growing, also it was observed that there were various sizes. These shrubs were planted in the community back in 2005, and since then are not produced in the community’s nursery. Currently, Pinus spp. and Polylepis spp. are the only trees that can be found at the nursery during winter. Therefore, to interpret the survey’s results and analyse the observed behaviour of the tolas in this area, a literature review of the propagation of the tolas Parastrephia quadrangularis and Baccharis tricuneata was carried out. Then, to highlight the benefits and limitations of these native shrubs known as “tolas” a literature review of potential uses in the management of ecosystems, in areas where forestry/agroforestry could work within the context of climate change. Although via surveys a glanced view of the importance, knowledge and uses that the community recognise for these shrubs.